Measuring the Informal Economy - Quiros-Romero, Gabriel (Policy Papers; Policy Paper, 2021)
This paper proposes a framework for measuring the informal economy that is consistent with internationally agreed concepts and methodology for measuring GDP. Based on the proposed framework, the informal economy 'comprises production of informal sector units, production of goods for own final use, production of domestic workers, and production generated by informal employment in formal enterprises.' This proposed framework will facilitate preparation of estimates of the informal economy as a component of GDP.